INVESTIGATION OF THE GLOBAL SOCIAL NETWORKING MARKET - Bochko , O.; Kuziak , V.; Aleksandraviciute, B. (The actual problems of regional economy development, 2020)
The article presents investigation on the global market of social networks. Timeliness of the topic is confirmed by the current conditions of the coronavirus pandemic, extension of the time spent in social networks and increased number of the social networks’ users. The goal of the research is to investigate the global social networking market. While writing the article the authors used the following research methods, particularly inductive and deductive – to collect, process and substantiate the information about the total number of social networks; economic analysis and comparison – to analyze the global social networking market; graphical – for visual demonstration of the web search queries for Facebook, Twitter, Pinterest Instagram; abstract-logical – for theoretical generalization and conclusion making. The article reveals the concept of the social networks Facebook, Twitter, Pinterest Instagram.The authors have conducted investigation on the global market of social networks by the platforms for the period of 2009-2020. It is determined that almost no one uses Stumble Upon, whereas in 2009 that network took 22.4% in the structure of all social networks in the world. Use of such social networks as Tumblr and Reditt tends to zero. The period of 2009-2020 is characterized by the increased interest to such social networks as Pinterest and Twitter. Particularly, in 2020, those networks have amounted for 10.45 and 14.33% in the structure of all social networks in the world respectively. Using Google Trend, the authors of the work have estimated the level of web search queries for «Twitter», «Pinterest» and social network «Facebook». Studying the web search queries for those notions in Ukraine, it is confirmed that particular activity was demonstrated by the Internet users searching for “Facebook” in the middle of 2017, and at the end of 2020, that search query is still the leading one. It is confirmed that the social network “Facebook” is also popular among Ukrainians. Scientific novelty of the article is in investigation of the social networking market, identification and substantiation of the strong tendencies of changing the index of coverage of the social media market by platforms, and forecast of the market shares of social networks by using economic-mathematical modeling. Forecast of the future tendencies for the nearest four years confirms the further positive dynamics concerning coverage by the social networks Facebook, YouTube, Instagram, Pinteres, Twitter, Tumblr.